Promoters of Orthologous Glycine max and Lotus japonicus Nodulation Autoregulation Genes Interchangeably Drive Phloem-Specific Expression in Transgenic Plants - Sureeporn Nontachaiyapoom; Paul T. Scott; Artem E. Men; Mark Kinkema; Peer M. Schenk; Peter M. Gresshoff (Molecular Plant-Microbe Interactions, 2007)
The nodule autoregulation receptor kinase (GmNARK) of soybean (Glycine max) is essential for the systemic auto-regulation of nodulation. Based on quantitative reverse-transcriptase polymerase chain reaction, GmNARK is expressed to varying levels throughout the plant; the transcript was detected at high levels in mature leaves and roots but to a lesser extent in young leaves, shoot tips, and nodules. The transcript level was not significantly affected by Bradyrhizobium japonicum during the first week following inoculation. In addition, the activities of the promoters of GmNARK and Lotus japonicus HAR1, driving a β-glucuronidase (GUSPlus) reporter gene, were examined in stably transformed L. japonicus and transgenic hairy roots of soybean. Histochemical GUS activity in L. japonicus plants carrying either a 1.7-kb GmNARKpr∷GUS or 2.0-kb LjHAR1pr∷GUS construct was clearly localized to living cells within vascular bundles, especially phloem cells in leaves, stems, roots, and nodules. Phloem-specific expression also was detected in soybean hairy roots carrying these constructs. Our study suggests that regulatory elements required for the transcription of these orthologous genes are conserved. Moreover, rapid amplification of 5′ cDNA ends (5′ rapid amplification of cDNA ends) revealed two major transcripts of GmNARK potentially originating from two TATA boxes. Further analysis of the GmNARK promoter has confirmed that these two TATA boxes are functional. Deletion analysis also located a region controlling phloem-specific expression to a DNA sequence between 908 bp and 1.7 kb upstream of the translation start site of GmNARK.